Auditory-Induced Emotion Mediates Perceptual Categorization of Everyday Sounds - Bergman, Penny; Västfjäll, Daniel; Tajadura-Jiménez, Ana; Asutay, Erkin (Frontiers in Psychology, 2016)
Research has shown that emotion categorization plays an important role in perception and categorization in the visual domain. In the present paper we investigated the role of auditory-induced emotions for auditory perception. We further investigated whether the emotional responses mediate other perceptual judgments of sounds. In an experiment, participants either rated general dissimilarities between sounds or dissimilarities of specific aspects of sounds. The results showed that a general perceptual salience map could be explained by both the emotional responses to, and perceptual aspects of, the sounds. Importantly, the perceptual aspects were mediated by emotional responses. Together these results show that emotions are an integral part of auditory perception that is used as the intuitive basis for categorizing everyday sounds.